Ethical Education Values in Balinese Women’s Traditional Clothing - Sudarsana, I Ketut (Cetta: Jurnal Ilmu Pendidikan, 2024)
Balinese traditional clothing is an essential element representing the Balinese’s cultural identity. More than just a body covering, these clothes are filled with ethical, aesthetic, and spiritual values that reflect the teachings of Hinduism. This research aimed to reveal the meaning and value behind the use of traditional clothing in religious ceremonies, especially among Balinese women. The research used a qualitative method with a direct observation approach to indigenous people. Data were collected through observation, in-depth interviews, and documentation, then analyzed descriptively. The results showed that traditional clothing is not only a symbol of respect for ancestors but also a symbol of purity, dignity, and respect for the gods. Balinese women adhere to a dress code emphasizing modesty, neatness, and color selection according to religious symbolism. In addition to showing physical beauty, traditional clothing reflects adherence and loyalty to Balinese Hindu teachings. Furthermore, traditional clothing plays a role in maintaining social harmony in indigenous communities. Each element of clothing has symbolism that reflects the relationship between humans, nature, and the gods. In conclusion, traditional Balinese clothing serves as a spiritual expression and a medium for preserving traditions and strengthening social relationships. Balinese women’s dress code in the traditional context reflects the harmonious balance between spirituality, tradition, and social interaction in Balinese life.